Gender bias in training of medical students in obstetrics and gynaecology: a myth or reality?. (March 2015) - Zahid, Akmal Z. Mohd; Ismail, Zaliha; Abdullah, Bahiyah; Daud, Suzanna
ABSTRACT: Objective: To investigate the experience of medical students during a clinical attachment in obstetrics and gynaecology (O&G). Study design: A questionnaire was distributed to medical students who completed their O&G posting between August 2012 and August 2013. The first part included basic demographic details (age, gender, and ethnicity) and frequency of actual clinical experience; the second part explored students' perception of their training and their relationship with other staff, in particular feeling of discrimination by specified groups of medical personnel. The responses were recorded using a Likert scale and were recategorised during analysis. Results: A total of 370 questionnaires were distributed, and 262 completed questionnaires were returned, giving a response rate of 71%. Female students had a significantly higher median (IqR) number of vaginal examinations performed 0.25(0.69) ( p = 0.002) compared to male students. Male students experienced a higher proportion of patient rejections during medical consultation, 87% vs. 32% of female students ( p < 0.001), a higher rate of refusal for clerking (71.4% vs. 57.5% of females, p = 0.035) and a higher rate of patients declining consent for internal examination (93.3% vs. 67.6% of females, p < 0.001). The majority of male students felt that their gender negatively affected their learning experience (87% vs. 27.4% of the female students, p < 0.001). Male students reported a significantly higher proportion of discrimination against their gender by medical officers ( p = 0.018) and specialists/consultants ( p < 0.001) compared to females but there was no discrimination between genders by staff nurses or house officers. A majority (58%) of female students stated an interest in pursuing O&G as a future career compared to 31.2% of male students. Conclusions: Our study confirmed that gender bias exists in our clinical setting as male students gain significantly less experience than female students in pelvic examination skills. We also demonstrated that compared to female students, male students experience higher levels of discrimination against their gender by trainers who are medical officers and specialists/consultants. Trainers must improve their attitudes towards male students, to encourage them and make them feel welcome in the clinical area. We must minimize gender discrimination and educational inequities experienced by male students, in order to improve their learning experience.